EFFICIENCY AND RELIABILITY OF MARKER ASSISTED SELECTION FOR RESISTANCE TO MAJOR BIOTIC STRESSES IN POTATO - Sood, Salej (Potato Journal, 2019)
Potato is an important food crop of the world. Its production is affected by both biotic and abiotic stresses. Here, in this study we screened 12 advanced generation hybrids including three check varieties for late blight, major potato viruses and Potato cyst nematode. The hybrids were phenol typed for late blight and viruses’ resistance. To confirm the resistance, the marker assisted selection was practiced using previously developed resistance markers for all the three biotic stresses. All the hybrids showed resistant reaction to late blight through detached leaf assay as well as whole plant resistance screening. Among checks, Kufri Girdhari was highly resistant whereas, Kufri Himalini was moderately resistant and Kufri Jyoti was susceptible to late blight. The ELISA results for viruses revealed that most of the hybrids were resistant to PVY, PLRV, PVS, PVM, PVA, while all were susceptible to PVX. Late blight resistant genes R1, R2 and R3a were present in two, three and six hybrids, respectively. Check variety, Kufri Jyoti was having R1 gene while Kufri Girdhari contained both R2 and R3a genes. The RYadg gene for PVY resistance was found in only LBY 18 and RYsto was found in all the hybrids and control varieties. The screening results for PVX gene linked molecular markers revealed that control variety, Kufri Himalini was positive for all four, the advanced hybrids SM/03-23, VMT 5-1, SM/05-75 and LBY18 for three and SM/00-42, SM/08-12 along with control variety, Kufri Girdhari were positive for two markers. All the hybrids showed the presence of SCG17 marker for PVS resistance and NI1127 for PLRV resistance except the control variety, Kufri Himalini for SCG17. The PCN resistance marker, Gro VI-XO2 was present in five hybrids and one check variety, Kufri Himalini, HC was present in six hybrids and two check varieties namely Kufri Jyoti and Kufri Girdhari. The R gene markers screening results were almost in agreement with phenotypic results except few cases. Therefore, we suggest their application in large scale high throughput preliminary screening for disease resistance followed by phenotypic validation of fewer genotypes.